Physicochemical and functional properties of sour starches from different cassava varieties - Onitilo, M.O.; Sanni, Lateef O.; Oyewole, O.B.; Maziya-Dixon, B.B. (Informa UK Limited, 2007)
This article reports our investigation on the effect of cassava varieties on the physicochemical and functional properties of sour starches. There were significant differences (P < 0.05) in the ash, pH, amylose, amylopectin, starch damage, total titratable acidity (TTA), sugar, and starch content but not moisture contents of various cassava sour starches. There were no significant differences (P > 0.05) in Water Absorption Capacity (WAC), swelling power, and solubility index, while significant differences were recorded in Least Gelation Concentration (LGC) and color at 5% level and granule size at P < 0.0001 for cassava sour starches. Peak viscosity values ranged from 333.17RVU (clone 4(2) 1425) to 380.75RVU (clone TME 1). There were significant differences (P < 0.05) in pasting properties except for pasting temperature and breakdown.